2008
DOI: 10.1001/archneur.65.7.958
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Findings of Ataxia With Oculomotor Apraxia Type 2 in 4 Families

Abstract: Background: Ataxia with oculomotor apraxia type 2 (AOA2) is an autosomal recessive disease caused by SETX mutations in 9q34 resulting in cerebellar ataxia in association with peripheral neuropathy, cerebellar atrophy on imaging, an elevated ␣-fetoprotein (AFP) serum level, and occasional oculomotor apraxia. Objective: To describe the clinical and molecular findings of 7 patients with a clinical presentation of AOA2 and their relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 15 publications
(13 reference statements)
0
34
0
6
Order By: Relevance
“…26 Sensorimotor axonopathy has been reported in AOA2 by a number of investigators. 3,4,6,11,12,15,22,27 However, as neither electromyographic (EMG) recordings of proximal muscles nor conduction studies of nerves of the proximal segments of the limbs were mentioned in those studies, and as somatosensory evoked potentials were documented only once, 4 it appears those studies did not aim to distinguish axonopathy from neuronopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Sensorimotor axonopathy has been reported in AOA2 by a number of investigators. 3,4,6,11,12,15,22,27 However, as neither electromyographic (EMG) recordings of proximal muscles nor conduction studies of nerves of the proximal segments of the limbs were mentioned in those studies, and as somatosensory evoked potentials were documented only once, 4 it appears those studies did not aim to distinguish axonopathy from neuronopathy.…”
Section: Discussionmentioning
confidence: 99%
“…14 The SETX gene has an open reading frame of 8031 nucleotides and 24 exons. 27 AOA2 has been associated with homozygous 3,4,6,11,12,19,21,23,31 and compound heterozygous 1,12,13,21,31 alterations that cause frameshift, nonsense, and missense mutations, and a restricted form of the disease resulted from two in cis-dominant SETX gene mutations. 5 Missense mutations in the SETX gene that cause ALS 4 cannot be distinguished at present from those that cause AOA2.…”
Section: Discussionmentioning
confidence: 99%
“…Features include onset between ages of 10 and 22 years (age ≤25 years), elevated serum AFP levels, peripheral neuropathy, occasional oculomotor apraxia and progressive cerebellar ataxia 7,8 . On the other hand, ataxia with oculomo- tor apraxia type 1 (AOA1) has different features such as early age at onset, normal serum AFP levels, and hypercholesterolemia and hypoalbuminemia 8 . In AOA2, oculomotor apraxia is an occasional and inconstant finding, while AFP is elevated in almost all patients (even if sometimes it is only in the upper range of normal values).…”
Section: Patientmentioning
confidence: 99%
“…The same study showed that the likelihood of missing a case using this cutoff was 0.23%, while the likelihood that a non-Friedreich ataxia, non-ataxia-telangiectasia ataxic patient might be affected with AOA2 was 46% 9 . Other mutations of SETX have been associated with the autosomal dominant form of juvenile amyotrophic lateral sclerosis (ALS4) 7,8 . Beyond the AFP level, when considering neuroimaging findings, both AT and AOA2 present cerebellar atrophy.…”
Section: Patientmentioning
confidence: 99%
“…5 To date, more than 50 mutations have been identified in AOA2 families worldwide. 1,2,[6][7][8][9][10][11][12] The mutations are distributed across the entire gene, without any specific mutation hot spots. Most of the mutations are frameshift, or nonsense mutations, supporting that a loss of function of SETX is critical for the development of AOA2.…”
mentioning
confidence: 99%